The impact of passive heat maintenance strategies between an active warm-up and performance: a systematic review and meta-analysis - Cowper, G.; Goodall, S.; Hicks, K.; Burnie, L.; Briggs, M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Prior to exercise, a warm-up routine has been suggested to be an imperative factor in task readiness with the anticipation that it will enhance performance. One of the key benefits of a warm-up is the increase in muscle and core temperature, which can be achieved in a variety of ways. An effective way to achieve improvements in core and muscle temperature is by performing an active warm-up. However, lengthy transition periods between an active warm-up and exercise performance are known to cause a decline in core and muscle temperature, thereby reducing performance capability. As such, methods are needed to assist athletes during transition periods, to maintain the benefits of a warm-up with the aim of optimising performance. Accordingly, the purpose of this review is to systematically analyse the evidence base that has investigated the use of passive heating to aide sporting performance when a transition period is experienced.